(untitled) (Eurasian Scientific Herald, 2025)
To study the immediate results of surgical correction of proximal femur deformity in children with ANFH after bloodless reduction of congenital hip dislocation. Materials and methods of the study. We observed 72 children aged 7 to 12 years with multiplanar deformities of the proximal femur in ANFH after bloodless reduction of congenital hip dislocation